Timpanogram pada Anak Usia 1-5 Tahun - Desti Kusmardiani; Wijana Wijana; Shinta Fitri Boesoirie; Sally Mahdiani (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACT Tympanometry is an objective examination that used to test condition of middle ear, mobility of tympanic membrane and the ossicles.The results are displayed in a curve called timpanogram. Timpanogram influenced by several factors, including age and race.The purpose of this study was to provide normal values of tympanogram in children aged 1 to 5 years. This study was an analytic research with cross sectional approach in 90 normal children aged 1-5 years through a routine examination with ear otoscopy and tympanometry. From the 90 samples (180 ears) the average value of the volume of the ear canal / Vea was 0.469 mL in the right ear and 0,495 mL in the left ear, the mean compliance / SAA 0.396 mL in the right ear and 0.380 mL in the left ear, and the average pressure / TPP -56.78 daPa on the right ear and the left ear daPa-53.26. Compared with the results of existing studies, the average value of the ear canal volume/ Vea and mean compliance/ SAA in children aged 1-5 years in Bandung showed lower. Statistically, in the Vea, there was a significant differences between men and women, with p = 0.041 in the right ear and p = 0.027 in the left ear. There was a correlation between variables Vea with SAA. Keywords: tympanogram, children ages 1-5 years.